Naturalistic analysis of tourist pedestrians’ spatial cognition - Gregoriades, Andreas; Dimitriou, Loukas (My University, 2020)
Urban pedestrians are the most vulnerable road users worldwide. The cause of pedestrian accidents is mainly attributed to human error, mental workload and situation awareness. Tourists belong to a special category of pedestrians that exhibit different behavior due to unfamiliarity with the environment, or the road traffic rules. Eye tracking technology has emerged as a popular method for addressing problems in pedestrian spatial cognition and decision making. However, most eye tracking studies, use stationary technology under a set of assumptions. These methods may miss out important properties that relate to environmental dynamics that cannot be accurately simulated in controlled settings, such as perception of environmental information in accordance to body movements and orientation. This work presents a naturalistic approach to pedestrian behavior analysis using mobile eye tracking technology. The paper present preliminary results and emphasizes on pedestrian workload estimation through pupil dilation and gaze analysis in 2 scenarios: road intersection under 2 different lighting conditions (night/day). Two categories of pedestrians are considered: tourists and resident users, to identify differences in workload levels and visual search behaviors among them under the effect of different lighting conditions. The paper presents an exploratory study with preliminary results.
Keywords: Cognitive Workload; Eye-tracking; Tourists behavior